2013
DOI: 10.4028/www.scientific.net/kem.594-595.996
|View full text |Cite
|
Sign up to set email alerts
|

Short Term and Long Term Aging Effects of Asphalt Binder Modified with Montmorillonite

Abstract: Abstract. Nowadays, most of asphalt used in pavement construction is produced from petrochemicals through refining process of crude oil. When evolves with time, asphalt become stiffer and brittle due aging process. In this paper, the rheological effect of short-term and long-term oxidative ageing of asphalt binder modified with montmorillonite (MMT) was studied using Superpave™ rotational viscometer (RV), dynamic shear rheometer (DSR) and Fourier transform infrared (FTIR) instruments. The results indicate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Since oxidation alters the bitumen composition, aging evaluation may be approached starting from the wellknown fractionation proposed by Corbett [9] in saturates, naphthene aromatics, polar aromatics, and asphaltenes, in the order of their increasing molecular polarity. The changes in bitumen chemical composition can be monitored through elemental and fractional analyses, or analytical techniques, such as infrared spectroscopy ( [1,10] and references therein, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]). As an example of aging index from FTIR, Cong et al [26] and Zhao et al [20] define a carbonyl index as…”
Section: Introductionmentioning
confidence: 99%
“…Since oxidation alters the bitumen composition, aging evaluation may be approached starting from the wellknown fractionation proposed by Corbett [9] in saturates, naphthene aromatics, polar aromatics, and asphaltenes, in the order of their increasing molecular polarity. The changes in bitumen chemical composition can be monitored through elemental and fractional analyses, or analytical techniques, such as infrared spectroscopy ( [1,10] and references therein, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]). As an example of aging index from FTIR, Cong et al [26] and Zhao et al [20] define a carbonyl index as…”
Section: Introductionmentioning
confidence: 99%
“…Hot Mix Asphalt (HMA) is a conventional mixture in road construction that are highly viscous, black, sticky, soluble in carbon disulphide and composed primarily of highly condensed polycyclic aromatic hydrocarbons which provide better in flexibility [1]. Materials for asphalt paving and standard structures must be complied with the requirements of standard specified by Highway Department in order to be sure that it's suitable to utilize and last long whilst highly safe for the users.…”
Section: Introductionmentioning
confidence: 99%
“…Materials for asphalt paving and standard structures must be complied with the requirements of standard specified by Highway Department in order to be sure that it's suitable to utilize and last long whilst highly safe for the users. However, HMA shows limitation on temperature, soften when the temperature is high and cracked when the temperature is low causing oxidation of asphalt because of aging process [1][2][3]. In addition, heavy traffic,high loading weight and wet tropical climatic conditions will damage the roads although these pavements are still in service cause large expenses for maintenance due to pavement distress [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of asphalt with polymers is one of the best options to improve asphalt properties [6]. The added polymer can strongly improve the binder properties, provide safer road, and reduce the maintenance cost by increasing the stiffness of the bitumen and by improving its temperature susceptibility [7]. Modarres and Hamedi [8] reported that the use of recycled waste plastic in pavement asphalt represents a valuable outlet for such materials.…”
Section: Introductionmentioning
confidence: 99%